2010
DOI: 10.1016/j.chemosphere.2010.01.029
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of persistent chlorinated and brominated organic contaminants in the European eel (Anguilla anguilla) in Irish waters

Abstract: The European eel (Anguilla anguilla) is a relatively high lipid, long lived species capable of living in a variety of brackish, fresh and marine habitats. As such, eels can accumulate organic pollutants and have been incorporated into environmental monitoring programs as a suitable "bioindicator" species for the determination of the levels of organic contaminants within different water bodies. The global eel stock is now in decline and while the cause of the collapse remains unidentified, it is likely to inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…Also in herring from the Baltic Sea (Karl and Ruoff, 2007) and in Polish eel (Szlinder-Richert et al, 2010), total toxicity is mainly determined by the 2,3,4,7,8-PentaCDF congener. Results from the Elbe in Germany, reported by Stachel et al (2006) revealed a predominance of the congeners 2, 3,4,7,1,2,3,4,7,2,3,6,7, In our study, OCDD was only detected in 5 of the 38 sites, similar as in Ireland (McHugh et al, 2010). OCDD belongs to the group of super-hydrophobic or super-lipophilic compounds and has a high bioaccumulation factor (Geyer et al, 2000).…”
Section: Mchugh Et Al (2010) Reported Concentrations In Irish Eel Wsupporting
confidence: 46%
See 2 more Smart Citations
“…Also in herring from the Baltic Sea (Karl and Ruoff, 2007) and in Polish eel (Szlinder-Richert et al, 2010), total toxicity is mainly determined by the 2,3,4,7,8-PentaCDF congener. Results from the Elbe in Germany, reported by Stachel et al (2006) revealed a predominance of the congeners 2, 3,4,7,1,2,3,4,7,2,3,6,7, In our study, OCDD was only detected in 5 of the 38 sites, similar as in Ireland (McHugh et al, 2010). OCDD belongs to the group of super-hydrophobic or super-lipophilic compounds and has a high bioaccumulation factor (Geyer et al, 2000).…”
Section: Mchugh Et Al (2010) Reported Concentrations In Irish Eel Wsupporting
confidence: 46%
“…Further research is required to identify these local sources. McHugh et al (2010) suggested point source influences of PCDDs at the Burrishoole catchment (Ireland) because eel showed more elevated PCDD levels than at four other catchments (Waterford, Mayo, Galway and Monaghan) where similar PCDD/Fs TEQ ratios were calculated. In a Japanese study on crucian carp (Carassius auratus (gibelio) langsdorfii) notable differences in the congener distribution ratios between different sampling areas were seen which could be dedicated to different sources of dioxin contamination (Kajiwara et al, 2007).…”
Section: Spatial Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] and from the Elbe in Germany [19]. Dioxin and dl-PCB levels were lower in the Loire (mean concentration 4.4 pg WHO 2005 PCDD/PCDF + dl-PCB TEQ/g, [7]) and in Irish rivers (0.49 to 4.9 pg WHO 1998 PCDD/PCDF + dl-PCB TEQ/g [27]). …”
Section: Nrwmentioning
confidence: 99%
“…After the preliminary preparation, fish tissues were subjected to different extraction procedures. Scientists often used Soxhlet extraction (SE) with different , Johnson-Restrepo et al 2008, Ueno et al 2006, Xian et al 2008, Su et al 2014, Hu et al 2011, Lankova et al 2013, He et al 2013, Zhang et al 2013, Jeong et al 2014, Roosens et al 2008, Roosens et al 2010, Losada et al 2009, McHugh et al 2010. The advantage for this extraction was high recovery values but extraction time was quite long and ranged from 4 to 48 h. Some of the researchers also used classic solvent extraction; nevertheless, recovery values were not always high enough and the consumption of solvents was high (Nyholm et al 2008, Asante et al 2013, Kim et al 2011.…”
Section: Introductionmentioning
confidence: 99%